2015
DOI: 10.1021/acs.jpcc.5b06441
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Intercalation in Graphene/MoS2 Composites: First-Principles Insights

Abstract: As a storage material for Li-ion batteries, graphene/molybdenum disulfide (Gr/MoS 2 ) composites have been intensively studied in experiments. But the relevant theoretical works from first-principles are lacking. In the current work, van-der-Waals-corrected density functional theory calculations are performed to investigate the interaction of Li in Gr/MoS 2 composites. Three interesting features are revealed for the intercalated Gr/Li(n)/MoS 2 composites (n = 1 to 9). One is the reason for large Li storage cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
56
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 60 publications
10
56
0
Order By: Relevance
“…It is obvious that MoS 2 /GR heterostructure exhibits markedly better electrochemical kinetic compared with MoS 2 /GR hybrid, well agreeing to the results of the CV measurement. The superior electrochemical kinetic of MoS 2 /GR heterostructure should be ascribed to the important role of MoS 2 /GR heterointerfaces in increasing the electronic conductivity of MoS 2 , enlarging the adsorption energy of Li‐ion on the surface of MoS 2 layer, and maintaining the high diffusion mobility of Li‐ion . Furthermore, the ultrasmall MoS 2 nanosheets can effectively shorten the Li‐ion transport path with more active sites for Li‐ion adsorption and reaction .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is obvious that MoS 2 /GR heterostructure exhibits markedly better electrochemical kinetic compared with MoS 2 /GR hybrid, well agreeing to the results of the CV measurement. The superior electrochemical kinetic of MoS 2 /GR heterostructure should be ascribed to the important role of MoS 2 /GR heterointerfaces in increasing the electronic conductivity of MoS 2 , enlarging the adsorption energy of Li‐ion on the surface of MoS 2 layer, and maintaining the high diffusion mobility of Li‐ion . Furthermore, the ultrasmall MoS 2 nanosheets can effectively shorten the Li‐ion transport path with more active sites for Li‐ion adsorption and reaction .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, several theoretical studies have revealed that the MoS 2 /GR atomic interface possesses an enhanced Li adsorption energy compared with MoS 2 sheets . The Li‐ions can diffuse faster between GR and MoS 2 layers with a lower diffusion barrier than that in MoS 2 interlayers . Moreover, MoS 2 /GR heterointerfaces can achieve a maximum intercalation at the ratio of 1 Li per Mo atom, this means the interlayer‐expanded MoS 2 resulting from the alternately stacked structure can possess an enhanced charge storage capability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first discharge curve also detected a plateau at 1.6 V, and this value is higher than the potential characteristic for the formation of Li x MoS 2 intercalates. Theoretical studies have shown that heterostructures consisted of MoS 2 and graphene (G) accommodate lithium between the layers . Such MoS 2 / x Li/G intercalates are more stable by 0.41 eV as compared to the Li x MoS 2 intercalates .…”
Section: Resultsmentioning
confidence: 99%
“…Graphene can be used as a carrier to prevent agglomeration of the MoS 2 sheet, so that the electrolyte is sufficiently in contact with the active material, improving the utilization ratio of the active material. Graphene also has good conductivity and high specific surface area, which can effectively improve the charge and discharge rate of MoS 2 …”
Section: Introductionmentioning
confidence: 99%